Law No. 21 of the year 2018 Amending Certain Provisions of the Penal Code As Promulgated by Law No. 58 of the year 1937 = قانون رقم 21 لسنة 2018 بتعديل بعض أحكام قانون العقوبات الصادر بالقانون رقم 58 لسنة 1937 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic